2019
DOI: 10.1103/physrevb.99.104428
|View full text |Cite
|
Sign up to set email alerts
|

Spin-order dependent anomalous Hall effect and magneto-optical effect in the noncollinear antiferromagnets Mn3XN with X=Ga , Zn, Ag, or Ni

Abstract: The anomalous Hall effect (AHE) and the magneto-optical effect (MOE) are two prominent manifestations of time-reversal symmetry breaking in magnetic materials. Noncollinear antiferromagnets (AFMs) have recently attracted a lot of attention owing to the potential emergence of exotic spin orders on geometrically frustrated lattices, which can be characterized by corresponding spin chiralities. By performing first-principles density functional calculations together with group-theory analysis and tight-binding mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 73 publications
3
40
0
Order By: Relevance
“…In this context, anti-perovskite manganese nitrides can be regarded as a new playground to explore the AH effect, since Mn 3 AN (A= Ni, Sn) have been found to show non-collinear AFM in the triangular Mn lattice corresponding to irreducible representations T 1g (Γ + 4 ) and T 2g (Γ + 5 ), respectively [13][14][15] and there are many analogues with the replaced nonmagnetic elements. A recent study on the spin-order dependent AH effect in the non-collinear AFM Mn 3 AN (A= Ga, Zn, Ag, or Ni) also suggested that these compounds are an excellent AFM platform for realizing novel spintronics applications 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, anti-perovskite manganese nitrides can be regarded as a new playground to explore the AH effect, since Mn 3 AN (A= Ni, Sn) have been found to show non-collinear AFM in the triangular Mn lattice corresponding to irreducible representations T 1g (Γ + 4 ) and T 2g (Γ + 5 ), respectively [13][14][15] and there are many analogues with the replaced nonmagnetic elements. A recent study on the spin-order dependent AH effect in the non-collinear AFM Mn 3 AN (A= Ga, Zn, Ag, or Ni) also suggested that these compounds are an excellent AFM platform for realizing novel spintronics applications 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the AHE has been predicted theoretically and confirmed experimentally in Mn based antiperovskite nitrides with the Γ 4g AFM order [29,[57][58][59][60]. Due to the AHC being odd with respect to the time reversal symmetry operation, reversal of the AFM order in the Γ 4g type antiperovskites is expected to change sign of the AHE (Fig.…”
mentioning
confidence: 88%
“…In this regard, noncollinear AFM materials [ 22 ] could provide a viable alternative to their collinear counterparts. Recent studies have shown that a number of high temperature noncollinear antiferromagnets, such as Mn 3 X (X = Ga, Ge, Sn or Ir) [ 23 -28 ] and antiperovskite ANMn 3 (A = Ga, Zn, Ag or Ni) [29][30][31] exhibit large anomalous Hall conductivities (AHC). Due to the AHC being odd with respect to time reversal symmetry, reversal of the Néel vectors [ 32 ] in these compounds is expected to change sign of the AHE that can be used as an efficient detection scheme of the AFM order using the standard Hall measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the AHE has been discovered in non-collinear antiferromagnets (Fig. 1(a)), such as Mn3X (X = Ga, Ge, Sn, or Ir) [23,24,25,26,27,28] and Mn3AN (A = Ga, Zn, Ag, or Ni) [29,30,31], and collinear antiferromagnets with specific arrangement of nonmagnetic atoms in the crystal lattice (Fig. 1(b)), such as CoNb3S6 [32,33,34].…”
mentioning
confidence: 99%